IMPLEMENTASI PROGRAM PENDAMPINGAN BELAJAR DIMASA PANDEMI BAGI SISWA SEKOLAH DASAR DI BALAI YATIH HJ. MARYAM - Septi Halwa Annada (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2021)
Currently, Indonesia has been hit by the corona virus since early 2020. This has an impact on several sectors of Indonesian stability, one of which is the education factor. Education that was originally carried out in schools face-to-face and interacting directly is now limited and carried out at home online. From this background the question arises how effective the implementation of teaching and learning is done at home or done online. In this study, the researcher uses a qualitative research method with the Participation Action Method approach which is a research model that is looking for something to link the research process into the process of social change. From the results of research conducted by researchers, it was found that learning carried out at home was considered less effective because elementary school students who were at Balai Yatim Hj. boredom experienced by students with learning at home.